Fluorescence evidence of annexin A6 translocation across membrane in model matrix vesicles during apatite formation. Issue 4 (20th April 2022) - Wang, Yubo; Weremiejczyk, Liliana; Strzelecka‐Kiliszek, Agnieszka; Maniti, Ofelia; Amabile Veschi, Ekeveliny; Bolean, Mayte; Ramos, Ana Paula; Ben Trad, Layth; Magne, David; Bandorowicz‐Pikula, Joanna; Pikula, Slawomir; Millán, Jose Luis; et al.
Abstract: Matrix vesicles (MVs) are 100–300 nm spherical structures released by mineralization competent cells to initiate formation of apatite, the mineral component in bones. Among proteins present in MVs, annexin A6 (AnxA6) is thought to be ubiquitously distributed in the MVs' lumen, on the surface of the internal and external leaflets of the membrane and also inserted in the lipid bilayer. To determine the molecular mechanism(s) that lead to the different locations of AnxA6, we hypothesized the occurrence of a pH drop during the mineralization. Such a change would induce the AnxA6 protonation, which in turn, and because of its isoelectric point of 5.41, would change the protein hydrophobicity facilitating its insertion into the MVs' bilayer. The various distributions of AnxA6 are likely to disturb membrane phospholipid organization. To examine this possibility, we used fluorescein as pH reporter, and established that pH decreased inside MVs during apatite formation. Then, 4‐(14‐phenyldibenzo[a, c]phenazin‐9(14H)‐yl)‐phenol, a vibration‐induced emission fluorescent probe, was used as a reporter of changes in membrane organization occurring with the varying mode of AnxA6 binding. Proteoliposomes containing AnxA6 and 1, 2‐Dimyristoyl‐ sn‐ glycero‐3phosphocholine (DMPC) or 1, 2‐Dimyristoyl‐ sn‐ glycero‐3phosphocholine: 1, 2‐Dipalmitoyl‐ sn‐ glycero‐3‐phosphoserine (DMPC:DPPS 9:1), to mimic the external and internal MV membrane leaflet, respectively, served as biomimetic models to investigate the nature of AnxA6 binding. Addition of Anx6 to DMPC at pH 7.4 and 5.4, or DMPC:DPPS (9:1) at pH 7.4 induced a decrease in membrane fluidity, consistent with AnxA6 interactions with the bilayer surface. In contrast, AnxA6 addition to DMPC:DPPS (9:1) at pH 5.4 increased the fluidity of the membrane. This latest result was interpreted as reflecting the insertion of AnxA6 into the bilayer. Taken together, these findings point to a possible mechanism of AnxA6 translocation in MVs from the surface of the internal leaflet into the phospholipid bilayer stimulated upon acidification of the MVs' lumen during formation of apatite.